Colonial Education and India, 1781-1945. (Milton)
1 online resource (472 p.)
Keywords: This 5-volume set tracks the various legal, administrative and social documentation on the progress of Indian education from 1780 to 1947. Thisfourth volume features commentaries, reports andpolicy documents from the period 1823-1920from an Indian perspective. The documents not only map a cultural history of English education in India but capture the debates in and around each of these domains through coverage of English (language, literature, pedagogy), the journey from school-to-university, and technical and vocational education. Produced by statesmen, educationists, administrators, teachers, Vice Chancellors and native national leaders, the documents testify to the complex processes through which colleges were set up, syllabi formed, the language of instruction determined, and infrastructure built. The sources vary from official Minutes to orders, petitions to pleas, speeches to opinion pieces. The collection contributes, through the mostly unmediated documents, to our understanding of the British Empire, of the local responses to the Empire and imperial policy and of the complex negotiations within and without the administrative structures that set about establishing the college, the training institute and the teaching profession itself.